2022
DOI: 10.1371/journal.pone.0271512
|View full text |Cite
|
Sign up to set email alerts
|

Pickering emulsion stabilized by palm-pressed fiber cellulose nanocrystal extracted by acid hydrolysis-assisted high pressure homogenization

Abstract: Palm pressed fibre (PPF) is a lignocellulose biomass generated from palm oil mill that is rich in cellulose. The present work aimed to combine acid hydrolysis followed by high-pressure homogenisation (HPH) to produce nanocrystal cellulose (CNC) with enhanced physicochemical properties from PPF. PPF was alkaline treated, bleached, acid hydrolysed and homogenised under high pressure condition to prepare CNC. The effects of homogenisation pressure (10, 30, 50, 70 MPa) and cycles (1, 3, 5, 7) on the particle size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Thus, the CNC-stabilized GEO-PE exhibited appreciably high stability (creaming index = 0). Previous research has also shown that CNC-stabilized emulsions showed low creaming index for 14 days at a wide range of pH indicating emulsion stability ( Ng et al, 2022 ). CNC increased the stability of the emulsion system by raising the viscosity of the continuous phase which is in accordance with Stoke's law ( Winuprasith and Suphantharika, 2015 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, the CNC-stabilized GEO-PE exhibited appreciably high stability (creaming index = 0). Previous research has also shown that CNC-stabilized emulsions showed low creaming index for 14 days at a wide range of pH indicating emulsion stability ( Ng et al, 2022 ). CNC increased the stability of the emulsion system by raising the viscosity of the continuous phase which is in accordance with Stoke's law ( Winuprasith and Suphantharika, 2015 ).…”
Section: Resultsmentioning
confidence: 94%
“…Consequently, the continuous phase may indirectly stabilize the droplets through entrapment. In the continuous phase, the CNC particles could potentially form a network, resulting in an increase in viscosity ( Ng et al, 2022 ). Cellulose crystals seem to influence both the area at the interface, which affects the stability of emulsion ( Meirelles et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ShiWan 100 prepared Pickering emulsions using the high-pressure homogenization method. The research results indicated that under the influence of different pH, temperature, and ion strengths, all emulsions prepared by high-pressure homogenization exhibited excellent stability.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Nanocrystal cellulose (CNC) from palm press fiber also used as pickering particle. CNC was obtained through combination of acid hydrolysis and high-pressure homogenization [21]. Pickering emulsion with 0,3% dosage of CNC exhibits large droplet but having a higher stability.…”
Section: Introductionmentioning
confidence: 99%